FCIs and economic activity: Some international evidence - Charles A. E. Goodhart; Boris Hofmann (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2003)
A Monetary Conditions Index (MCI), a weighted average of the short-term real interest rate and the real exchange rate, is a commonly used indicator of aggregate demand conditions. In-sample evidence for the US, the euro area, Japan and the UK suggests that a Financial Conditions Index (FCI), also comprising property prices and share prices, would be a better indicator for economic activity than the standard MCI. Out-of sample the FCI also performs better than the MCI, but its overall performance is mixed. An FCI would have predicted the recent economic downturn in Japan and the UK, but not in the US and the euro area.
Keywords: 330; Monetärer Indikator; Immobilienpreis; Börsenkurs; Konjunkturindikator; Schätzung; USA